Accurate Symbolic Steady State Modeling of Buck Converter - Eko Setiawan; Takuya Hirata; Ichijo Hodaka (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Steady state analysis is fundamental to any electric and electronic circuit design. Buck converter is one of most popular power electronics circuit and has been analyzed in various situations. Although the behavior of buck converters can be understood approximately by the well-known state space averaging method, little is known in the sense of detailed behavior or exact solution to equations. In this paper a steady state analysis of buck converter is proposed which allows the exact calculation of steady state response. Our exact solution is expressed as a Fourier series. Our result is compared with numerical calculation to be verified. Our method copes with more complicated problems such as describing average power and root-mean-square power that are most critical issues in power electronics circuit.